Pd/SAPO-34 passive NOx adsorbers: Stable Pd ion adsorption sites in six-member rings. (15th March 2021) - Zhang, Nana; Xin, Yin; Li, Ruirui; Han, Dongxu; Jia, Junxiu; Li, Qian; Wang, Jin; Zhang, Zhaoliang
Abstract: Pd/zeolites with chabazite (CHA) topology are effective passive NO x adsorbers (PNAs), which are promising for the removal of NO x from diesel exhausts during cold start to meet increasingly stringent emission regulations. In this work, Pd/SAPO-34 zeolites with different preparation methods and Pd contents were developed and exhibited high NO adsorption performance. Three Pd species in Pd/SAPO-34, including well-dispersed PdO x clusters, Pd ions in the eight- and six-member rings (8MRs and 6MRs) of zeolites, are NO adsorption sites in the absence of H2 O in the feed, demonstrated by a good linear relationship between the total Pd contents and NO x desorption amounts. However, in the presence of H2 O, only Pd ions in 6MRs are stable NO adsorption sites and provide the continuous NO adsorption, due to the limited mobility of the Pd ions in 6 MRs with small pore size. This new finding points out a definite direction for the rational design of high-performance PNAs to eliminate NO x during the cold start of diesel vehicles.